Assessing analytical methods to monitor isoAsp formation in monoclonal antibodies - Eakin, Catherine M.; Miller, Amanda; Kerr, Jennifer; Kung, James; Wallace, Alison (Frontiers in Pharmacology, 2014)
A ubiquitous post-translational modification observed in proteins is isomerization of aspartic acid to isoaspartic acid (isoAsp). This nonenzymatic post-translational modification occurs spontaneously in proteins and plays a role in aging, autoimmune response, cancer, neurodegeneration and other diseases. Formation of isoAsp is also a significant issue for recombinant monoclonal antibody based protein therapeutics particularly when isomerization occurs in a complementarity-determining region (CDR) due to potential impact to the clinical efficacy. Here, we present and compare three analytical methods to monitor and/or quantify isoAsp formation in a monoclonal antibody. The methods include two peptide map based technologies with quantitation from either UV integration or total ion peak areas, as well as an alternative approach using IdeS digestion to generate Fc/2 and Fab’2 regions, followed by HIC to separate the population of Fab’2 containing an isoAsp. The level of isoAsp detected by the peptide map and the digested-HIC methods presented here show similar trends although sample throughput varies by method.